The influence of some factors on the production of alcohol whisky by Saccharomyces cerevisiae MS42 from barley malt - Quyen, Nguyen Van; Thao, Nguyen Quang; Anh, Nguyen Thao; Dat, Nguyen Thanh (Vietnam Journal of Biotechnology, 2018)
Fermented wine is a complex process including many chain reactions to convert sugar into alcohol, CO2, the byproduct and energy. Fermentation processes and product quality depend on the fermentation conditions. The objective of this study is to find the a good condition for effective fermentation to produce good quality distillation and less toxins and impurities. Currently, the production technology of wine or beer in the world and in Vietnam is diverse, there are many different techniques to optimize production in order to create optimal products. Each technology depends on the scale of production, climatic characteristics, materials, strains used in fermentation,.... On this topic we focus on some basic factors affect on fermentation alcohol use barley malt, yeast Saccharomyces cerevisiae MS42 include: pH, temperature, concentration SO2 in the fluid of fermentation, the yeast cell count to the initial seed, sugar, kinetics of fermentation alcohol barley malt on the medium. The creteria for selection of optimal factors is based on the production of alcohol, toxic compounds, contaminants, cell biomass. The products produced sensory board for evaluation, combined analysis of chromatography on toxin components and impurities according to standard TCVN 7043: 2013. Carry out the fermentation experiments in 1000ml of fluid to determine optimal conditions, then perform experimental fermentation under the conditions of industrial production on a 500 liter scale. The optimal conditions for barley malt fermentaion by S. cerevisiae MS42 was: medium pH= 4.5-5.0; To= 25-30oC; K2S2O5: 0.2 - 0.3 (g/l); the starting seed: 7-10%; sugar content: 140 – 160 g/l; fermentation time for 132 to 138 hours